RNA-sequencing approach for exploring the protective mechanisms of dexmedetomidine on pancreatic injury in severe acute pancreatitis - Yao, Jiaqi; Lan, Bowen; Ma, Chi; Liu, Yan; Wu, Xiaoqi; Feng, Kaixuan; Chen, Hailong; Wen, Qingping (Frontiers in Pharmacology, 2023)
Background. Severe acute pancreatitis (SAP) is a severe form of acute pancreatitis with the potential to cause life-threatening complications. Patients with acute SAP require surgical intervention and are admitted to the intensive care unit for non-invasive ventilation. Dexmedetomidine (Dex) is currently used by intensive care clinicians and anaesthesiologists as an adjunctive sedative. Therefore, the clinical availability of Dex makes it easier to implement in SAP treatment than developing new drugs. Methods. Randomly dividing thirty rats into sham-operated (Sham), SAP, and Dex groups. The severity of pancreatic tissue injury in each rat was assessed by Hematoxylin and eosin (HE) staining. Serum amylase activity and inflammatory factor levels were measured using commercially available kits. The expressions of necroptosis-related proteins, myeloperoxidase (MPO), CD68, and 4-hydroxy-trans-2-nonenal (HNE) were detected using immunohistochemistry (IHC). Transferase-mediated dUTP nick-end labeling (TUNEL) staining was utilized to identify pancreatic acinar cell apoptosis. The subcellular organelle structure of pancreatic acinar cells was observed using transmission electron microscopy. The regulatory effect of Dex on the gene expression profile of SAP rat pancreas tissue was investigated using RNA sequencing. We screened for differentially expressed genes (DEGs). Quantitative real-time PCR (qRT-PCR) measured critical DEG mRNA expression in rat pancreatic tissues. Results. Dex attenuated SAP-induced pancreatic injury, infiltration of neutrophils and macrophages, and oxidative stress. Dex inhibited the expression of necroptosis-associated proteins RIPK1, RIPK3, and MLKL and alleviated apoptosis in acinar cells. Dex also mitigated the structural damage caused by SAP to mitochondria and endoplasmic reticulum. Dex inhibited SAP-induced 473 DEGs, as determined by RNA sequencing. Dex may regulate SAP-induced inflammatory response and tissue damage by inhibiting the toll-like receptor/nuclear factor κB (TLR/NF-κB) signaling pathway and neutrophil extracellular trap formation. Conclusions. This study elucidated the remarkable effect of Dex against SAP and investigated the potential mechanism of action, providing an experimental base for the future clinical application of Dex in the treatment of SAP.